Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/svn-2016-000031
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the SUMO pathway for neuroprotection in brain ischaemia

Abstract: Small ubiquitin-like modifier (SUMO) conjugation (SUMOylation) is a post-translational protein modification that modulates almost all major cellular processes, and has been implicated in many human diseases. A growing body of evidence from in vitro and in vivo studies demonstrates that increasing global levels of SUMO conjugated proteins (global SUMOylation) protects cells against ischaemia-induced damage, while suppressing global SUMOylation promotes cell injury after ischaemia. Indeed, SUMOylation has emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 55 publications
0
38
0
7
Order By: Relevance
“…Transient brain ischemia is a severe form of metabolic stress that triggers dramatic activation of SUMO2/3 conjugation, and to a lesser extent, SUMO1 conjugation (Yang et al, 2014). It has been proposed that this is a protective response that shields neurons from damage induced by ischemia (Yang et al, 2008a, 2016; Lee and Hallenbeck, 2013). Indeed, results from in vitro and in vivo studies support this notion.…”
Section: Introductionmentioning
confidence: 99%
“…Transient brain ischemia is a severe form of metabolic stress that triggers dramatic activation of SUMO2/3 conjugation, and to a lesser extent, SUMO1 conjugation (Yang et al, 2014). It has been proposed that this is a protective response that shields neurons from damage induced by ischemia (Yang et al, 2008a, 2016; Lee and Hallenbeck, 2013). Indeed, results from in vitro and in vivo studies support this notion.…”
Section: Introductionmentioning
confidence: 99%
“…Not unexpectedly, a growing number of studies have linked SUMOylation in several diseases. Alterations in SUMOylation have been implicated in a wide range of diseases including cancers, diabetes, cardiovascular disease, and neuropathologies such as Huntington's disease, Parkinson's disease, Progeria syndrome, brain ischemia, and Alzheimer's disease . Furthermore, Gupta and colleagues have also shown that the SUMO E2‐conjugating enzyme UBC9‐dependent increased SUMOylation could promote autophagy, and hence, may represent a novel strategy to modulate cardiac functions in compromised hearts .…”
Section: A Role For Sumoylation In the Maintenance Of Genomic Integrimentioning
confidence: 99%
“…Alterations in SUMOylation have been implicated in a wide range of diseases including cancers, diabetes, cardiovascular disease, and neuropathologies such as Huntington's disease, Parkinson's disease, Progeria syndrome, brain ischemia, and Alzheimer's disease. [57][58][59][60][61][62] Furthermore, Gupta and colleagues have also shown that the SUMO E2-conjugating enzyme UBC9-dependent increased SUMOylation could promote autophagy, and hence, may represent a novel strategy to modulate cardiac functions in compromised hearts. [60] In addition, SUMOylation has been shown to modulate the immunogenic responses upon host-pathogen interaction, including the effect on NF-B and interferon pathways, as evidenced by the many infectious agents that target the host's SUMOylation machinery.…”
Section: A Role For Sumoylation In the Maintenance Of Genomic Integrimentioning
confidence: 99%
“…Major efforts have been invested in screening for specific SENP inhibitors via both in silico and conventional high-throughput screening methods (54,55). However, few of these screens have identified candidates with medicinal properties and have made use of physiologically relevant substrates (54).…”
Section: Discussionmentioning
confidence: 99%
“…Major efforts have been invested in screening for specific SENP inhibitors via both in silico and conventional high-throughput screening methods (54,55). However, few of these screens have identified candidates with medicinal properties and have made use of physiologically relevant substrates (54). Accordingly, in this study, we miniaturized an AlphaScreen-based qHTS assay to a 1536well format designed to screen for inhibitors of the isopeptidase activity of SENPs and used an endogenous SUMO-conjugated protein substrate and the conserved SENP catalytic domain (40).…”
Section: Discussionmentioning
confidence: 99%